PENGARUH PENGHINDARAN PAJAK, VOLATILITAS ARUS KAS OPERASI DAN UKURAN PASAR TERHADAP PERILAKU BIAYA ASIMETRIS - Rahmadani Aji Putra; Dul Muid (Diponegoro Journal of Accounting, 2020)
The study to examine the effect of tax avoidance, operating cash flow volatility, and market size on asymmetric cost behavior. The sample used in study was manufacturing companies listed on the Indonesia Stock Exchange (IDX) during period (2015-2018). Total sample of 208 companies. Data collection using purposive sampling method analysis with linier regression. And the result of study tax avoidance has a significant negative effect on asymmetric cosh behavior, operating cash flow volatility has a significant positive on asymmetric cosh behavior, and market size has a significant negative effet on asymmetic cosh behavior.